Cuerpo tirano y tiranizado (2009)
ABSTRACT: When the mind is subverted by the body uncritically, this become in a tyrant, it overturns the reality and obsses; but once that makes the subject acts accordingly, can pass from perpetrator to victim and be tyrannized: sucked, irradiated, cut, sewing and numbed. Multiple reasons argue the users of Plastic Surgery of reduction and body shaping to submit to the first, generally those are foreing and alienating causes without know that taken the first step may fall into a dependency of unexpected consequences.